ATR inhibitors as a synthetic lethal therapy for tumours deficient in ARID1A - Chris T. Williamson (Nature Portfolio, 2016)
Mutations in the BAF SWI/SNF complex subunits are frequent in cancers but selective therapeutic approaches are not available yet. Here, the authors demonstrate that defects ofARID1Aand other subunits sensitizes cancer cells to the DNA checkpoint kinase inhibitor ATR in a synthetic lethal manner.